The Influence Of Professional Skepticism and Auditor Competence To The Quality Of Remote Audits During The Covid-19 Pandemic (Case Study at Inspektorat Jenderal Kementerian Keuangan) - Salsa Dila Ridwanto; Ahmad Syarief (Indonesian Accounting Literacy Journal, 2022)
This study aims to determine the effect of professional skepticism and auditor competence to remote audit quality. This type of research is called descriptive quantitative. Respondents in this study were the Auditors of the Inspectorate General of the Ministry of Finance, amounting to 50 people using a probability sampling technique. The sources of data in this study are primary and secondary data. Primary data was taken through questionnaires and analyzed by using the multiple linear regression analysis method after testing the validity, reliability, and classical assumption test. Furthermore, the data will be processed using the SPSS version 25.0 program application. The results of this study indicate simultaneously and partially that professional skepticism and auditor competence have a positive and significant effect on remote audit quality. The results of the coefficient of determination show that simultaneously professional skepticism and auditor competence have a positive and significant effect on the quality of long-distance audits of 67,5%. The results of the regression coefficients show that partially professional skepticism has a positive and significant effect of 43,5%, while auditor competence has a positive and significant effect of 57,2%. This means that professional skepticism and auditor competence together are very important for an auditor in maintaining the quality of the remote audits he conducted during the COVID-19 pandemic.